The simplified expression of (√12+6)(-√8-√2) is -6√6 - 18√2
<h3>How to simplify the radical?</h3>
The expression is given as:
(√12+6)(-√8-√2)
Factor out -1
(√12+6)(-√8-√2) = -(√12+6)(√8+√2)
Expand the expression
(√12+6)(-√8-√2) = -(√96 + 6√8 + √24 + 6√2)
Evaluate the radicals
(√12+6)(-√8-√2) = -(4√6 + 12√2 + 2√6 + 6√2)
Evaluate the like terms
(√12+6)(-√8-√2) = -(6√6 + 18√2)
Open the bracket
(√12+6)(-√8-√2) = -6√6 - 18√2
Hence, the simplified expression of (√12+6)(-√8-√2) is -6√6 - 18√2
Read more about radicals at:
brainly.com/question/1980062
#SPJ1